A case of alport syndrome with pregnancy-related atypical hemolytic uremic syndrome, andcrescentic glomerulonephritis - BERKE MENTEŞE, İLAY; TUĞCU, MURAT; VELİOĞLU, ARZU; TUĞLULAR, ZÜBEYDE SERHAN (My University, 2021)
BACKGROUND: Thrombotic microangiopathy (TMA) is one of the most important complications in pregnant patients with chronic kidney disease (CKD) causing clinical deterioration. However, little is known about the pregnancy course in women with Alport syndrome (AS). CASE: A 28-week pregnant, 22-year-old woman was admitted to our clinic because of widespread edema. Her medical history was notable only for hearing impairment. On examination, vital signs were normal except for the blood pressure (150/90 mmHg). There were diffuse crackles at the lung bases, and 3þ pitting edema in both legs. Lab results revealed heavy proteinuria with 11 gr/day and isomorphic erythrocytes with granular casts in microscopic urine examination. An emergency c-section was performed due to severe preeclampsia at 30 weeks’ gestation. After delivery, her edema did not improve, serum creatinine and lactate dehydrogenase levels elevated, anemia and thrombocytopenia developed (Table 1). Additional tests revealed negative Coombs test, schistocytes on peripheral smear and normal ADAMTS13 level. There was no pathology in serological studies. She received four sessions of plasmapheresis therapy, and with the diagnosis of aHUS, eculizumab therapy was started. Despite improving thrombocytopenia and anemia, serum creatinine levels continued to rise and her urine output decreased. A kidney biopsy was performed (Figure 1). In the light microscopy, 11 of 15 glomeruli had circumferential cellular crescents and 4 had partial cellular crescents. The sample had no findings consistent with TMA. No staining was seen with IgG, IgA, IgM, C3, C1q, j and k in immunofluorescence.